Call the name of the night. 1 - Mitsuboshi, Tama (Yen Press, 2023)
"Deep in the forest, a curious pair reside: a young girl Mira, whose affliction leads her to call forth darkness whenever she's in distress; and her physician Rei, determined to seek a cure. Each day, she works to remember the light and bring back the person she used to be. But a sudden visit from Rei's friend, who harbors an interest in Mira's illness may be end of their peaceful days... " --